Europe organisée, Europe du libre-échange? : fin 19e siècle - années 1960 - Bussière, Éric; Dumoulin, Michel; Schirmann, Sylvain (Bruxelles : P.I.E. Peter Lang, 2006)
Bibliotheek François Vercammen
Frans
Monografie